Pengaruh Hope dan Peer Attachment terhadap Grit Mahasiswa Universitas Buana Perjuangan Karawang - Fahri Ahmad Fauzi; Linda Mora; Holy Greata Singadimedja (EduInovasi: Journal of Basic Educational Studies, 2025)
University students face various academic, social, and psychological challenges that demand a high level of perseverance to endure and complete their studies. This study aims to analyze the influence of hope and peer attachment on grit among students at Universitas Buana Perjuangan Karawang. The research employed a quantitative causal design, with a population of 11,352 students and a sample of 386 participants selected using a convenience sampling technique. The instruments used included the State Hope Scale (SHS), the Inventory of Parent and Peer Attachment (IPPA), and the Short Grit Scale (Grit-S). Data were analyzed using tests of normality, linearity, multiple regression, and the coefficient of determination. The analysis results showed that both hope and peer attachment had a significant influence on grit, both partially and simultaneously. Hope and peer attachment together explained 63.1% of the variance in grit, with peer attachment contributing more substantially (56.2%) compared to hope (6.8%). These findings highlight the importance of strengthening both hope and peer connections as strategic efforts to enhance students' grit.